Preparation method of light-driven magnesium-based composite hydrogen storage material
By combining surface-modified strontium titanate with magnesium-based materials, the photo-driven magnesium-based composite hydrogen storage material is prepared, which solves the problems of high dehydrogenation temperature and large energy consumption of magnesium-based hydrogen storage materials, and realizes efficient solar-driven storage Hydrogen process.
Patent Information
- Application Number
- CN202411604884.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-11
- Publication Date
- 2025-02-18
AI Technical Summary
The high thermodynamic stability and slow kinetic properties of existing magnesium-based hydrogen storage materials lead to high dehydrogenation temperatures and consume a lot of energy, limiting their large-scale commercial applications.
Surface-modified strontium titanate is used as the photoresponse catalyst, combined with a magnesium-based material, and a photo-driven magnesium-based composite hydrogen storage material is prepared by high-energy ball milling method, and the dehydrogenation process of hydrogen storage material is driven by solar energy.
It significantly improves the dehydrogenation performance of the photo-driven magnesium-based composite hydrogen storage material, reduces the dehydrogenation temperature and energy consumption, and improves the efficient conversion efficiency of solar-hydrogen energy.
Smart Images

Figure CN119461242A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of hydrogen storage materials, and in particular relates to a method for preparing a light-driven magnesium-based composite hydrogen storage material. Background Art
[0002] With the increasing demand for energy in human society, the extensive use of traditional fossil energy such as oil and coal has caused serious problems such as energy depletion, global warming and environmental pollution. In the long run, the most fundamental means is to focus on the development of clean renewable energy and the use of green secondary energy. As a secondary energy source, hydrogen energy is considered to be one of the ideal energy carriers for sustainable development in the future due to its advantages such as high element abundance, environmental friendliness and high combustion calorific value. The United States, Japan, the European Union and other countries have successively issued "Hydrogen Energy Development Strategies and Plans", proposing to build an industrial chain for hydrogen production, storage, transportation and utilization, and promote the development of the "hydrogen economy". However, due to the special problems of hydrogen such as low density, low energy density per unit volume, flammability, explosion and leakage, efficient storage and transportation are the key bridges connecting the upstream hydrogen production and downstream hydrogen application, and are an important link affecting the large-scale development of hydrogen energy.
[0003] Compared with traditional high-pressure gaseous storage and transportation, magnesium-based solid hydrogen storage materials represented by light metal hydride magnesium hydride (MgH2) have the advantages of higher volumetric hydrogen storage density (110g / L) and mass hydrogen storage density (7.6wt.%), high efficiency, safety and high economy (magnesium resources are abundant), and have the potential for large-scale application. However, the high thermodynamic stability and slow kinetic performance lead to the dehydrogenation temperature of MgH2 as high as 300-400℃, and the enthalpy change is 74.5kJ / mol H2, which is equivalent to consuming 31% of the hydrogen energy, which seriously restricts its large-scale commercial application. The traditional resistance heating method currently used, the heat source is mainly through heat conduction, convection heat transfer and other methods, the heating process is slow, the material is heated unevenly, and the energy utilization rate is low. On the other hand, it is necessary to use modification strategies such as catalysis, nano-sizing and alloying to regulate the poor dehydrogenation kinetics of magnesium-based hydrogen storage materials to achieve rapid absorption and release of hydrogen at lower temperatures. Therefore, there is an urgent need to develop an energy supply method that is efficient, environmentally friendly and can effectively improve the effectiveness of existing modification strategies, so as to promote the large-scale application of magnesium-based hydrogen storage materials.
[0004] Solar energy is a renewable, efficient, green primary energy source. It comes from the sun’s surface at 5762K, and the radiation energy density reaching the earth’s surface is about 1.36kW / m 2, relative to the average temperature of about 300K on the earth's surface, its quality coefficient is as high as 0.95. In recent years, the development of photothermal conversion technology has injected new impetus into the efficient use of solar energy. The absorption efficiency of sunlight has been greatly improved through internal photoresponsive materials, and the target temperature has been reached in a short time. Based on this, if an efficient photoresponsive magnesium-based composite hydrogen storage material can be constructed, solar energy can be used to drive the dehydrogenation of the hydrogen storage material, and the efficient conversion of solar energy to hydrogen energy can be achieved, it has important scientific research value and application prospects. However, MgH2, as an indirect bandgap insulator, has a bandgap width of 4.9eV-5.6eV. When illuminated, the energy of the incident photon is difficult to excite the valence electrons of the material to transition across the Fermi level into the conduction band to form photogenerated carriers, resulting in the self-photolysis of MgH2 (MgH2+hv→Mg+H2 or MgH2+hv→Mg 2+ +2e - (VH)+H2) almost never occurs. Furthermore, the photothermal effect of MgH2 itself is not significant, the photothermal conversion efficiency is low, and the heat brought by light cannot promote its decomposition and dehydrogenation. Therefore, it is necessary to add other light-responsive catalysts to prepare magnesium-based composite hydrogen storage materials. On the one hand, the incident photons excite the redox potential generated by the separation of catalyst valence electrons and holes to induce the decomposition and dehydrogenation of MgH2; on the other hand, magnesium-based composite hydrogen storage materials have a stronger photothermal effect, rapidly heat up under light, and accelerate the dehydrogenation kinetics.
[0005] Among various semiconductor photocatalytic materials (titanium dioxide, cadmium sulfide, g-C3N4, etc.), AB3 perovskite strontium titanate exhibits a variety of advantages that match magnesium-based hydrogen storage materials: (1) Strontium titanate has a large bandgap (3.2-3.5 eV), which can form a large redox potential that matches the decomposition potential of MgH2; (2) Strontium titanate has high electrical and thermal conductivity, which can enhance the transmission efficiency of photogenerated carriers and heat between the catalyst and magnesium-based materials. (3) The large bandgap of strontium titanate can effectively reduce the recombination of photogenerated electrons and holes, greatly improving the utilization rate of light energy.
[0006] Therefore, combining strontium titanate as a light-responsive catalyst with magnesium-based materials will produce an ideal light-driven magnesium-based composite hydrogen storage material. However, there are few reports on the research of this material in magnesium-based hydrogen storage materials, especially the modification and optimization of the light-responsive catalyst strontium titanate in magnesium-based composite materials and the analysis of the photothermal coupling mechanism of composite hydrogen storage materials. Therefore, there is still a lot of room for research on how to prepare efficient light-driven magnesium-based composite hydrogen storage materials. Summary of the invention
[0007] In view of the above-mentioned defects of the prior art, efficient light-driven magnesium-based composite hydrogen storage materials are still rare, which seriously restricts the practical application of light-driven MgH2 dehydrogenation technology. In order to solve the above-mentioned technical problems, the present invention provides a method for preparing a light-driven magnesium-based composite hydrogen storage material using surface-modified strontium titanate as a light-responsive catalyst, which realizes the regulation of the surface modification of strontium titanate, and the preparation and testing of the dehydrogenation performance of the light-driven magnesium-based composite hydrogen storage material.
[0008] In a first aspect, the present invention provides a method for preparing a light-driven magnesium-based composite hydrogen storage material, comprising the following steps:
[0009] (1) Preparation of STO-450 particles
[0010] Strontium titanate and sodium borohydride are mixed and ground in a mortar; then, the mixture is heated and calcined in a tube furnace under an argon atmosphere to perform surface modification treatment; then, the calcined product is washed and vacuum dried to obtain surface reconstructed STO-450 particles;
[0011] (2) Preparation of light-driven magnesium-based composite hydrogen storage materials
[0012] MgH2 and STO-450 particles were mixed by high-energy ball milling to prepare a MgH2-Ywt.% STO-450 composite hydrogen storage material, wherein Y is the mass fraction of STO-450 particles in the composite hydrogen storage material.
[0013] In some embodiments, in step (1), the mass ratio of strontium titanate to sodium borohydride is 4:1.
[0014] In some embodiments, in step (1), strontium titanate and sodium borohydride are mixed and ground for 20 minutes.
[0015] In some embodiments, in step (1), the argon gas flow rate in the tube furnace is 100 mL / min.
[0016] In some embodiments, when the mixture of strontium titanate and sodium borohydride in step (1) is heated in an argon atmosphere, the heating rate is 5°C / min; preferably, the calcination temperature is 400-500°C, more preferably 450°C; further preferably, the calcination time is 60 min.
[0017] In some embodiments, in step (1), the calcined product is centrifugally washed, and 60°C hot water and anhydrous ethanol are used as solvents; preferably, the parameters of the centrifugal washing are: centrifuge speed 8000 rpm, centrifugation time 10 min / time. The order of solvent addition is once hot water, once ethanol, and a total of three times.
[0018] In some embodiments, in step (1), the washed product is vacuum dried at 80° C. for 24 hours to obtain STO-450 particles.
[0019] In some embodiments, in step (2), the mass ratio of MgH2 to STO-450 particles is 9:1-1:1, such as 9:1, 7:3 and 1:1; preferably, in MgH2-Ywt.%STO-450, Y is 30.
[0020] In some embodiments, in step (2), the rotation speed of the high-energy ball mill is 300 rpm, the ball-to-material ratio is 60:1, and the ratio of large, medium and small grinding balls is 3:4:3; preferably, during the high-energy ball milling process, the forward rotation is 30 minutes, the reverse rotation is 30 minutes, and the machine is stopped for 20 minutes, with a total ball milling time of 480 minutes.
[0021] In a second aspect, the present invention provides a light-driven magnesium-based composite hydrogen storage material obtained by the above preparation method.
[0022] In some embodiments, the dehydrogenation amount of the light-driven magnesium-based composite hydrogen storage material reaches 0.681 wt.%.
[0023] Beneficial effects of the present invention:
[0024] (1) The surface reconstruction of the STO-450 particles prepared by the present invention is attributed to the oxidation-reduction reaction of hydrogen produced by the decomposition of sodium borohydride on the surface of strontium titanate during the heat treatment, which introduces a nano-disordered layer. Due to the presence of the disordered layer, the absorption edge of the STO-450 particle surface to light extends to the infrared region, thereby enhancing the photothermal effect of the photoresponsive catalyst. The radiation intensity is 0.576W / cm 2 After 5 minutes of natural light illumination, the surface temperature of STO-450 particles reached 189°C (154°C for strontium titanate particles), and the surface temperature of the light-driven magnesium-based composite hydrogen storage material reached 171°C (142°C for commercial high-energy ball-milled MgH2). Compared with traditional resistance furnace heating, the heating rate of the light-driven magnesium-based composite hydrogen storage material prepared by the present invention has been greatly improved, achieving efficient solar thermal conversion and high energy utilization.
[0025] (2) Due to the presence of the disordered layer on the surface, Ti with different valence states (such as Ti 3+ and Ti 2+) coexist in STO-450, which improves the charge transfer and hydrogen molecule transport rate between the STO-450 and MgH2 interface during the dehydrogenation of the light-driven magnesium-based composite hydrogen storage material; furthermore, compared with strontium titanate, new defect energy levels and (multivalent Ti site) impurity energy levels are introduced into the band gap of STO-450, which exhibit different donor and acceptor properties under ionization, resulting in the upward shift of the conduction band and valence band of STO-450, thereby improving the reduction ability of photogenerated electrons to MgH2 under photon excitation.
[0026] (3) Due to the synergistic effect between the enhancement of the above-mentioned photothermal effect, the improvement of the charge transfer efficiency and the increase in the reduction potential of the photogenerated electrons, the STO-450 particles prepared by the present invention can greatly improve the dehydrogenation performance of the light-driven magnesium-based hydrogen storage material. 2 Under the test conditions of 5 hours of natural light illumination, the dehydrogenation amount of commercial high-energy ball-milled MgH2 was only 0.042%; compared with the dehydrogenation amount of 0.378wt.% of MgH2-30wt.% strontium titanate composite hydrogen storage material, the dehydrogenation amount of MgH2-30wt.% STO-450 composite hydrogen storage material reached 0.681wt.%, an increase of nearly 2 times. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1 1 is an X-ray diffraction diagram of strontium titanate and STO-450 particles according to an embodiment of the present invention.
[0028] Figure 2 1 and 1 are scanning electron microscope images of strontium titanate and STO-450 particles according to an embodiment of the present invention, wherein (a) is strontium titanate and (b) is STO-450 particles.
[0029] Figure 3 1 and 1 are transmission electron microscope images of strontium titanate and STO-450 particles according to an embodiment of the present invention, wherein (a) is strontium titanate and (b) is STO-450 particles.
[0030] Figure 4 It is an X-ray diffraction diagram of the MgH2-30wt.% STO-450 light-driven magnesium-based composite hydrogen storage material according to an embodiment of the present invention.
[0031] Figure 5 It is a transmission electron microscope image of the MgH2-30wt.% STO-450 light-driven magnesium-based composite hydrogen storage material according to an embodiment of the present invention.
[0032] Figure 6 The strontium titanate, STO-450 particles, commercial high-energy ball-milled MgH2 and MgH2-30wt.% STO-450 light-driven magnesium-based composite hydrogen storage material of the present invention are subjected to a radiation intensity of 0.576W / cm 2Temperature curve under natural light.
[0033] Figure 7 The commercial high-energy ball-milled MgH2, MgH2-30wt.% strontium titanate and MgH2-30wt.% STO-450 light-driven magnesium-based composite hydrogen storage material of the present invention is subjected to a radiation intensity of 0.576W / cm 2 Light-driven dehydrogenation curves under natural light illumination.
[0034] Figure 8 The radiation intensity is 0.576W / cm 2 Comparison of the dehydrogenation capacity of the MgH2-30wt.% STO-450 light-driven magnesium-based composite hydrogen storage material under natural light illumination for 5 hours and the dehydrogenation capacity of the pure heat-driven magnesium-based composite hydrogen storage material when the temperature rises due to the photothermal effect. DETAILED DESCRIPTION
[0035] The following describes several preferred embodiments of the present invention with reference to the drawings in the specification, so that the technical content is clearer and easier to understand. The present invention can be embodied in many different forms of embodiments, and the protection scope of the present invention is not limited to the embodiments mentioned in the text.
[0036] Example 1
[0037] (1) Preparation of STO-450 particles
[0038] Strontium titanate and sodium borohydride were mixed in a mass ratio of 4:1 and ground in a mortar for 20 minutes; then, in a tube furnace, under an argon atmosphere (argon flow rate of 100 mL / min), the mixture was heated to 450°C at a heating rate of 5°C / min and kept warm for 60 minutes for surface modification; then, the calcined product was centrifugally washed with 60°C hot water and anhydrous ethanol, the speed was set to 8000 rpm, the time was 10 min / time, one hot water, one ethanol, and washed 3 times; finally, vacuum dried at 80°C to obtain surface reconstructed STO-450 particles.
[0039] (2) Preparation of light-driven magnesium-based composite hydrogen storage materials
[0040] MgH2-30wt.% STO-450 composite hydrogen storage material was prepared by mixing commercial MgH2 and STO-450 particles in a mass ratio of 7:3 by high-energy ball milling. During the high-energy ball milling process, the rotation speed was 300rpm, the ball-to-material ratio was 60:1, and the ratio of large, medium and small grinding balls was 3:4:3. The ball milling process was forward for 30 minutes, reverse for 30 minutes, and stopped for cooling for 20 minutes, with a total time of 480 minutes.
[0041] The X-ray diffraction patterns of strontium titanate and STO-450 particles used in this example are as follows: Figure 1 shown.
[0042] The scanning electron microscope images of the strontium titanate and STO-450 particles used in this example are as follows: Figure 2 As shown, (a) is strontium titanate, and (b) is STO-450 particles. After calcination, the surface reconstructed STO-450 particles still retain the original morphology of the original strontium titanate (polyhedron shape with a flat cross section).
[0043] Transmission electron microscope images of strontium titanate and STO-450 particles used in this example, where (a) is strontium titanate and (b) is STO-450 particles. After surface modification, the lattice fringes of STO-450 become blurred, and a disordered layer with a thickness of about 2nm appears, indicating that the surface of STO-450 is reconstructed.
[0044] The X-ray diffraction pattern of the MgH2-30wt.% STO-450 light-driven magnesium-based composite hydrogen storage material prepared in this example is as follows: Figure 4 The transmission electron microscope image is shown in Figure 5 shown.
[0045] Testing the photo-driven dehydrogenation performance of photo-driven magnesium-based composite hydrogen storage materials
[0046] The light-driven dehydrogenation performance of MgH2-30wt.% STO-450 light-driven magnesium-based composite hydrogen storage material was tested: Strontium titanate, STO-450 catalyst particles, commercial high-energy ball-milled MgH2 and light-driven magnesium-based composite hydrogen storage material were tested at a radiation intensity of 0.576W / cm 2 The temperature under natural light illumination; the initial pressure of the light-driven dehydrogenation test is 0 bar, and the heat is provided by the photothermal effect of the light-driven magnesium-based composite hydrogen storage material itself. The target temperature is the temperature of the light-driven magnesium-based composite hydrogen storage material under the radiation intensity of 0.576W / cm 2 The temperature under natural light; the light source providing natural light is Shanghai Bofeilai Microsolar 300 xenon lamp; the thermocouple used for temperature test is Capeson high-precision K-type thermocouple GG-K-30; the PCT equipment used for hydrogen storage performance test is the domestic HPSA-auto high-pressure gas adsorption instrument.
[0047] The results show that the radiation intensity is 0.576W / cm 2After 5 minutes of natural light illumination, the surface temperature of STO-450 particles reached 189°C (154°C for strontium titanate particles), and the surface temperature of light-driven magnesium-based composite hydrogen storage materials reached 171°C (142°C for commercial high-energy ball-milled MgH2). The dehydrogenation amount of MgH2-30wt.% STO-450 composite hydrogen storage material reached 0.681wt.%.
[0048] Comparative Example 1:
[0049] Preparation of STO-400 / 450 / 500 particles
[0050] The calcination temperature in step (1) of Example 1 is adjusted to 400°C and 500°C, and the other conditions or parameters are consistent with Example (1), and the obtained STO-400 and STO-500 particles are obtained. A higher treatment temperature corresponds to the degree of surface reconstruction. Due to incomplete surface reconstruction, the former has a low degree of improvement in the photothermal effect, charge transfer efficiency and band gap regulation of the strontium titanate material itself, and STO-400 cannot match the MgH2 photodehydrogenation reaction well; the latter has an overload of surface reconstruction, which makes the concentration of the disordered layer too high. The photogenerated electrons and holes generated by STO-500 under illumination will directly recombine on the surface of the STO-500 particles, and the concentration of photogenerated carriers used to induce the MgH2 photodehydrogenation reaction will decrease, and the catalytic effect will be reduced. Compared with STO-450, the calcination temperature of the surface treatment of both has room for optimization.
[0051] Comparative Example 2:
[0052] The STO-450 doping amount in step (2) of Example 1 was reduced to 10 wt.%, and other conditions or parameters were consistent with those in Example (2), to obtain the MgH2-10 wt.% STO-450 light-driven magnesium-based composite hydrogen storage material at a radiation intensity of 0.576 W / cm 2 Under natural light, the temperature brought by the photothermal effect is 159±0.4℃, and the light-driven dehydrogenation amount is 0.5wt% in 5 hours. Both the temperature and dehydrogenation performance are lower than those of MgH2-30wt.% STO-450 light-driven magnesium-based composite hydrogen storage material.
[0053] Comparative Example 3:
[0054] The high temperature calcination treatment in step (1) of Example 1 was omitted, and the strontium titanate particles were directly subjected to high-energy ball milling with MgH2. The other conditions or parameters were consistent with those in step (2) of Example 1, and a MgH2-30wt.% strontium titanate light-driven magnesium-based composite hydrogen storage material was obtained.
[0055] The same light-driven dehydrogenation performance test method was used, and the radiation intensity was 0.576W / cm 2Within 5 hours of natural light illumination, the dehydrogenation amount of MgH2-30wt.% strontium titanate light-driven magnesium-based composite hydrogen storage material was 0.378wt.%, but the dehydrogenation amount of MgH2-30wt.% STO-450 light-driven magnesium-based composite hydrogen storage material was 0.681wt.%. In comparison, the photoresponsive catalytic performance of strontium titanate without any surface modification was low, and after surface modification, the dehydrogenation amount increased by nearly 2 times.
[0056] Comparative Example 4:
[0057] In the high-energy ball milling process of step (2) of the embodiment, STO-450 was not added, and other conditions or parameters were consistent with those of step (2) of the embodiment, and a high-energy ball milled material of pure commercial MgH2 was obtained. 2 Under natural light, the temperature brought by the photothermal effect is 138±0.6℃, and the light-driven dehydrogenation amount is 0.08wt% in 5 hours. Its temperature and dehydrogenation capacity are lower than those of MgH2-30wt.% STO-450 light-driven magnesium-based composite hydrogen storage material.
[0058] In the examples and comparative examples, commercial high-energy ball-milled MgH2, MgH2-30wt.% strontium titanate and MgH2-30wt.% STO-450 light-driven magnesium-based composite hydrogen storage materials were subjected to a radiation intensity of 0.576W / cm 2 The temperature curve under natural light illumination and the light-driven dehydrogenation curve are shown as follows: Figure 6 and Figure 7 shown.
[0059] Figure 8 The radiation intensity is 0.576W / cm 2 The comparison chart of the dehydrogenation capacity of MgH2-30wt.% STO-450 light-driven magnesium-based composite hydrogen storage material under natural light illumination for 5 hours and the dehydrogenation capacity of pure heat-driven magnesium-based composite hydrogen storage material when the temperature rises due to the photothermal effect proves that the dehydrogenation behavior of the light-driven magnesium-based composite hydrogen storage material is mainly dominated by light.
[0060] The preferred specific embodiments of the present invention are described in detail above. It should be understood that ordinary technicians in the field can make many modifications and changes based on the concept of the present invention without creative work. Therefore, all technical solutions that can be obtained by technicians in the technical field based on the concept of the present invention through logical analysis, reasoning or limited experiments on the basis of the prior art should be within the scope of protection determined by the claims.
Claims
1. A method for preparing a light-driven magnesium-based composite hydrogen storage material, comprising the following steps: (1) Preparation of STO-450 particles Strontium titanate and sodium borohydride are mixed and ground in a mortar; then, the mixture is heated and calcined in a tube furnace under an argon atmosphere to perform surface modification treatment; then, the calcined product is washed and vacuum dried to obtain surface reconstructed STO-450 particles; (2) Preparation of light-driven magnesium-based composite hydrogen storage materials MgH2 and STO-450 particles were mixed by high-energy ball milling to prepare a MgH2-Ywt.% STO-450 composite hydrogen storage material, wherein Y is the mass fraction of STO-450 particles in the composite hydrogen storage material.
2. The preparation method according to claim 1, wherein In step (1), the mass ratio of strontium titanate to sodium borohydride is 4:
1.
3. The preparation method according to claim 1, wherein In step (1), strontium titanate and sodium borohydride are mixed and ground for 20 minutes.
4. The preparation method according to claim 1, wherein In step (1), the argon gas flow rate in the tube furnace is 100 mL / min.
5. The preparation method according to claim 1, wherein In step (1), the calcination temperature is 400-500° C. and the calcination time is 60 min.
6. The preparation method according to claim 1, wherein In step (1), the calcined product is centrifugally washed, and 60° C. hot water and anhydrous ethanol are used as solvents.
7. The preparation method according to claim 1, wherein In step (1), the washed product is vacuum dried at 80° C. for 24 h to obtain STO-450 particles.
8. The preparation method according to claim 1, wherein In step (2), the mass ratio of MgH2 to STO-450 particles is 9:1-1:
1.
9. The preparation method according to claim 1, wherein In step (2), the rotation speed of the high energy ball mill is 300 rpm, the ball to material ratio is 60:1, and the ratio of large, medium and small grinding balls is 3:4:
3.
10. A light-driven magnesium-based composite hydrogen storage material obtained by the preparation method according to any one of claims 1 to 9.